Pengembangan multimedia pembelajaran praktik individu instrumen pokok dasar siswa SMK di bidang keahlian karawitan - Ismalik Perwira Admadja; Eko Marpanaji (Jurnal Pendidikan Vokasi, 2016)
Penelitian ini bertujuan untuk: (1) menghasilkan multimedia pembelajaran pada mata pelajaran praktik individu instrumen pokok dasar, (2) mengetahui kelayakan multimedia pembelajaran pada mata pelajaran praktik individu instrumen pokok dasar, dan (3) mengetahui peningkatan hasil belajar siswa menggunakan multimedia pembelajaran pada mata pelajaran praktik individu instrumen pokok dasar. Metode penelitian yang digunakan adalah metode penelitian dan pengembangan dengan desain model pengembangan Stephen M. Alessi dan Stanley R. Trollip. Langkah-langkah pengembangannya yaitu: (1) perencanaan; (2) desain; dan (3) pengembangan. Teknik analisis data untuk uji coba produk menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa: (1) ditinjau dari aspek media dinilai "Sangat Baik" dengan skor 4,27 oleh ahli media;(2) ditinjau dari aspek materi dinilai "Sangat Baik" dengan skor 4,47 oleh ahli materi; (3) ditinjau dari aspek penggunaan dinilai "Sangat Baik" dengan skor 4,23 oleh siswa; (4) peningkatan hasil belajar siswa menunjukkan kenaikan rerata skor siswa kelas yang menggunakan multimedia sebesar 31,53 sedangkan kelas yang tidak menggunakan multimedia meningkat sebesar 20,11. Kata kunci: pengembangan, pembelajaran, multimedia pembelajaran, kelayakan. DEVELOPING LEARNING MULTIMEDIA OF INDIVIDUAL PRACTICE IN FUNDAMENTAL MUSIC INSTRUMENT FOR SMK STUDENTS IN THE EXPERTISE OF KARAWITAN Abstract The purposes of this research were: (1) to produce multimedia learning on the subject of individual practice in fundamental music instrument; (2) to determine the appropriateness of the learning multimedia in the subject of individual practice in fundamental music instrument; and (3) to determine the improvement in the students' learning outcomes from the use of multimedia in teaching the subject of individual practice in fundamental music instrument.This research was a research and development, with the development model design by Alessi and Trollip. The development stages were as follows: (1) planning; (2) design; and (3) development. The data of the try-out of the product was analyzed using descriptive statistics. The results showed that: (1) the media aspects were rated "very good" with a score of 4.27 by the media expert; (2) the material aspects were rated "very good" with a score of 4.47 by the materials expert; (3) the aspects of using product were rated "very good" with a score of 4.23 by the students; (4)the improvement of the students' learning outcomes in the class using the multimedia showed a mean score increase of 31.53 which was greater than that of the nonmultimedia class which was only 20.11. Keywords: development, learning, learning multimedia, appropriateness